Antibacterial Activity of Bidara Arab Leaves (Ziziphus spina-christi L) Extract Against Gram-negative Anaerobic Subgingival Bacteria - Syahriel, Dwis; Hervina, Hervina; Sardi, Ni Wayan Arni (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Gram-negative anaerobic subgingival bacteria play an important role in the initiation and progression of periodontitis. The secondary metabolites contained in Bidara Arab leaves (Ziziphus spina-christi L) have potential to be antibacterial and inhibited the growth of pathogenic bacterial. The purposed of this study to evaluated the antibacterial activity of Bidara Leaves extract against gram-negative anaerobic subgingival bacteria. Method: Experimental laboratories using Mueller hinton agar to determine the antibacterial activity of Bidara leaves extract 40% and 60% against Porphyromonas gingivalis, Aggregatibacter ctinomycetemcomitans, and Fusobacterium nucleatum, with a comparison of the negative control group ethanol 96% and tetracycline as positive control. The production of extracts through maseration techniques and the subsequent phytochemical testing through tube reaction test. Result: The results of phytochemical analysis identified the presence of flavonoids, tannins, saponins, steroids. The inhibition test showed that the Bidara leaves extract exhibited strong inhibition and a concentration of 60% was more effective than 40% against Gram-negative anaerobic subgingival bacteria including Porphyromonas gingivalis, Aggregatibacter ctinomycetemcomitans, and Fusobacterium nucleatum. Conclusion: The Bidara Arab leaves (Ziziphus spina-christi L) extract at concentration 60% was more effective than 40% against gram-negative anaerobic bacteria